If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(5 + -2x) + -1 = 6(4 + -1x) + -3x + -5 (5 * 4 + -2x * 4) + -1 = 6(4 + -1x) + -3x + -5 (20 + -8x) + -1 = 6(4 + -1x) + -3x + -5 Reorder the terms: 20 + -1 + -8x = 6(4 + -1x) + -3x + -5 Combine like terms: 20 + -1 = 19 19 + -8x = 6(4 + -1x) + -3x + -5 19 + -8x = (4 * 6 + -1x * 6) + -3x + -5 19 + -8x = (24 + -6x) + -3x + -5 Reorder the terms: 19 + -8x = 24 + -5 + -6x + -3x Combine like terms: 24 + -5 = 19 19 + -8x = 19 + -6x + -3x Combine like terms: -6x + -3x = -9x 19 + -8x = 19 + -9x Add '-19' to each side of the equation. 19 + -19 + -8x = 19 + -19 + -9x Combine like terms: 19 + -19 = 0 0 + -8x = 19 + -19 + -9x -8x = 19 + -19 + -9x Combine like terms: 19 + -19 = 0 -8x = 0 + -9x -8x = -9x Solving -8x = -9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9x' to each side of the equation. -8x + 9x = -9x + 9x Combine like terms: -8x + 9x = 1x 1x = -9x + 9x Combine like terms: -9x + 9x = 0 1x = 0 Divide each side by '1'. x = 0 Simplifying x = 0
| 4(x-9)-3x=3(x-2)-4 | | 4(x+2)=5(x+6) | | F=8/5(n-27) | | 5(x+15)=10 | | 4x^2+16x-7=0 | | 3/5-3.6 | | x/7+3=6 | | 5(4y-6)-6=-6(y-7) | | 3x-16+3x=3+6x-18 | | 3x+41-4x=2-6x+4 | | 30-(x+5)=8x-2 | | x(x+5)=2x+5 | | 15/h+35=95 | | 35+15/h=95 | | 5m^2-38m-16=0 | | 6+a=10 | | 12x-3=32x+12 | | x/5+5=305 | | A=3b+2 | | -1/2x=1048 | | 0.2+13=1.3-14.5 | | 6+3q=9+2q | | 13-37= | | 10x^2+10x-20=0 | | 2y-2=-6 | | 2y-3=-6 | | X+3=-x+12 | | 2(m-10)+2=24 | | (x+12)(x-2)=1 | | 2x+3=2y-7 | | 2x+6y=-12 | | 7(7-5x)=-38-6x |